The relation of body mass index, menopausal symptoms, and lipid profile with bone mineral density in postmenopausal women - Ismail Alay; Cihan Kaya; Huseyin Cengiz; Sukru Yildiz; Murat Ekin; Levent Yasar (Elsevier, 2020)
Objective: We aimed to evaluate the relationship of menopausal symptoms, body mass index (BMI), and serum lipid profile with Bone Mineral Density (BMD) levels. Materials and methods: 452 postmenopausal women were included in this case-control study at our outpatient clinic between January 2012 and January 2015. The patients were stratified according to their BMD, based on dual-energy X-ray absorptiometer (DXA) results, as the normal group (−1 ≤ T-score), osteopenia group (−2.5 < T-score < −1), and osteoporosis group (T-score ≤ −2.5). High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), total cholesterol (TC), and triglycerides (TG), fasting plasma glucose (FPG) levels were measured. To assess the menopausal symptoms, the Menopause Rating Scale (MRS) questionnaire was used. Results: Waist circumference (WC) and BMI were significantly lower in the osteoporosis group than in normal and osteopenia groups (p: 0.001, p: 0.001, respectively). L2-L4 measurements were negatively correlated with Low Density Lipoprotein (LDL) levels, but positively correlated with WC. BMI showed significant positive correlation with Femur Neck (FN), L1-L2, and L2-L4 measurements. Among menopausal symptoms, there was a significant negative correlation between heart discomfort and L1-L2 levels. On multiple regression analysis, a relation between FN scores and somatic symptom scores was identified. Conclusion: Hyperlipidemia, lower BMI, lower WC, and severe somatic symptoms may be associated with decreased BMD. Keywords: Body mass index, DXA scan, Lipids, Menopause, Osteoporosis